The Hubungan Kelengkapan Rekam Medis Terhadap Akurasi Pengkodean ICD-10 dan ICD-9 - Annisa Wahyuni; Nurul Fitri Khumaira; Siska Siska (J-REMI : Jurnal Rekam Medik dan Informasi Kesehatan, 2024)
The completeness of medical records is an important factor that affects the quality of data and coding accuracy. Based on the initial survey at the 'Aisyiyah General Hospital, found from 20 medical records still 75% completeness of filling in the incoming and outgoing summary sheets, the absence of anamnesis and diagnosis results, and 60% completeness of the doctor's item recording component. The purpose of this study was to find out the relationship between the completeness of medical record documents with the accuracy of the ICD-10 and ICD-9 coding. This study used descriptive and inferential quantitative methods with a population of 638 documents, and the number of samples of 84 files uses simple random techniques. The frequency of filling in the medical record document is incomplete 89.3%, the duration of the ICD-10 code is 26.2% and the ICD-9 CM was 32.2%. The analysis results showed that there was no significant relationship between the completeness of medical record documents and the accuracy of the ICD-10 and ICD-9 coding (P-Value > 0.05). Complete medical records tend to have more accurate coding, while incomplete medical records often cause errors in coding. The importance of maintaining the completeness of medical records to increase coding accuracy has a positive impact on the management of health data, clinical decision-making, and health insurance claims. Efforts to increase the completeness of medical records, such as training in medical staff and effective electronic system implementation, are recommended to ensure better coding quality.